The Influence of CSR on Customer Loyalty with Trust and Customer Satisfaction as Mediating Variables at PT. Swen Inovasi Transfer - Rindi Handayani; Heti Mulyati; Ma’mun Sarma (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the impact of Corporate Social Responsibility (CSR) on customer loyalty, mediated by customer trust and satisfaction, at PT. Swen Inovasi Transfer, which implements a CSR program in the form of biogas digester assistance. The program seeks to introduce biogas as an environmentally friendly renewable energy source and to raise public awareness of the importance of clean energy. This research employs SEM-PLS analysis to examine the direct and indirect effects of CSR on customer loyalty. The findings reveal that CSR has a significant positive impact on customer satisfaction and loyalty, and it can enhance loyalty through increased satisfaction. However, customer trust was not found to have a significant effect on loyalty. These findings suggest that effective CSR programs should incorporate efforts to enhance customer satisfaction in order to build sustainable loyalty, with a particular emphasis on transparency and product quality.